Konservatisme Akuntansi, Konsentrasi Kepemilikan dan Tanggung Jawab Sosial - Setiawan, Yan Christianto; Mettan, Santho Vlennery (E-Jurnal Akuntansi, 2022)
The quality of financial statements can be seen through the characteristics adopted, one of which is conservatism. In addition to conservatism, Corporate Social Responsibility (CSR) is also a form of the company's commitment to all stakeholders. This study aims to examine the relationship between conservatism and CSR performance, which is moderated by concentration of ownership and macroeconomic conditions. The research population is business entities that go public and are listed on the IDX, which publish sustainability reports during the 2018-2020 period. The number of samples is 123 years of observation. The sampling technique of this research used purposive sampling technique. The analysis of the hypothesis test used is a random effect model on the panel data structure. The results show that accounting conservatism has a positive effect on CSR. The existence of macroeconomic conditions can strengthen the influence of accounting conservatism on CSR performance. However, the concentration of ownership weakens this influence. Keywords: Conservatism; CSR; Ownership; Macroeconomic